Implementation of extreme programming in developing a payroll system for freelance workers in the construction industry - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research focuses on improving the payroll system for casual laborers in the construction industry to address the efficiency challenges posed by payment complexity and dynamic changes in company needs. The method applied was Extreme Programming (XP), a software development approach that emphasizes team collaboration, responsiveness to change, and continuous testing. The results showed that implementing XP successfully improved the efficiency of payroll system development, ensured the accuracy of salary calculations, and provided responsiveness to company policy changes. The resulting application includes features of employee profile management, automatic salary calculation, working hour monitoring, user stories for payroll changes, payroll dashboard, payroll history, tax and deduction management, salary payment notifications, payroll reports, and integration with financial systems. This research contributes to developing a responsive and efficient payroll system, improving the human resource management process in the construction industry. The pilot test results and user acceptance analysis showed the success of this application, with a user satisfaction rate of 79%. Thus, this research significantly contributes to improving the efficiency of the payroll system, presenting a solution suitable for the dynamics of the construction industry, and improving the experience of casual labor employees and the company's operational efficiency.